2011
DOI: 10.1002/sia.3442
|View full text |Cite
|
Sign up to set email alerts
|

Sputtered molecular fluoride anions: HfFn and WFn

Abstract: The emission of negatively charged HfF n − (n ≤ 5) and WF n − (n ≤ 7) molecular ions sputtered from a mixed Hf-W-PbF 2 fluoride sample by a 13 keV Cs + ion beam was studied. The emitted ions were detected in a high-sensitivity double-focusing secondary ion mass spectrometer. In the HfF n − and WF n − series, HfF 5 − and WF 6 − are the anions formed most abundantly, with their ratio amounting to HfF 5 − /WF 6 − ∼6, whereas HfF 5 − /WF 5 − ∼18. In particular, the rather high yield of the HfF 5 − anion could be e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…The O 2 results obtained in this ISAMS work provide an on‐line isobar separation tool for the AMS measurement of 182 HfF 5 − , additional to the natural depletion of WF 5 − observed when the fluorinating agent PbF 2 is not used . However, the reaction mechanisms (the differences among O 2 , NO 2 , N 2 O, and possibly O 3 ), and the rate of reactions as a function of ion energy, must be studied further.…”
Section: Resultsmentioning
confidence: 85%
See 2 more Smart Citations
“…The O 2 results obtained in this ISAMS work provide an on‐line isobar separation tool for the AMS measurement of 182 HfF 5 − , additional to the natural depletion of WF 5 − observed when the fluorinating agent PbF 2 is not used . However, the reaction mechanisms (the differences among O 2 , NO 2 , N 2 O, and possibly O 3 ), and the rate of reactions as a function of ion energy, must be studied further.…”
Section: Resultsmentioning
confidence: 85%
“…[7,10,17] However, the reaction mechanisms (the differences among O 2 , NO 2 , N 2 O, and possibly O 3 ), and the rate of reactions as a function of ion energy, must be studied further. The design of the isobar separator system also needs to be improved towards these challenging goals so that it will be able to: (1) transport and retard full beams of rare analyte anions, with normal extraction energies from Cs + sputter ion sources and with no arbitrary phase space limitation; (2) accept all retarded anions and deliver them with a small average energy and narrow energy range; and (3) finely control the anion energy throughout the gas cell so that the average ion energy could be maintained, within a narrow range, just above the threshold for the intended reactions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Secondly, even for a constant ion source acceleration voltage, there is considerable variation in the energy (and hence axial momentum) of the emerging ions and the distribution of this energy shows quite different patterns for atomic in comparison with molecular anions. An example of this distribution for 12 C -ions and their multimers is given in Figure 3 of ref [24] and for F -, HF 5 -and WF 6 -, in Figure 3 of ref [25]. In both these cases, the atomic anions have a large amplitude high energy tail (~0.001 of the peak maximum at 100 eV above the central ion energy), but little low energy tail; the molecular anions show almost no high energy tail, but a smaller but significant low energy tail (~10-4 of the peak maximum at 100 eV below the central ion energy).…”
Section: Entrance Ion Optics Design For the Next Generation Systemmentioning
confidence: 99%
“…In an additional application, Hf and W fluoroanions were generated from the PbF 2 matrix. Since HfF 5 − and WF 5 − were both formed, there was still a problem with overlap of isobaric isotopic ions, which cause interference problems for the measurement of extreme isotope ratios by AMS . However, it was found that the tungsten species could be attenuated by reaction with O 2 or NO 2 , enabling measurement of the trace isotopes of Hf.…”
mentioning
confidence: 99%